First Order and Second Order Universal Filter Using Four Terminal Floating Nullor - Tarunkumar, Huirem; Ranjan, Ashish; Meitei Pheiroijam, Nonglen (International Journal of Engineering and Technology, 2018)
A new lower order voltage mode namely first order and second order filter employing a Four terminal floating nullor (FTFN) is reported using a single schematic structure. The proposed filter uses two FTFN block along with passive components for the realization of first order filter as well as second order filter. The frequency response of proposed filter depends on the voltage input and switches present in it. Realization of both first order and second order filter have advantage features incorporating no component adjustment, absence of non-ideal behaviour and low sensitivity. PSPICE simulations are well performed using 0.35 µm CMOS process provided by Austrian Micro Systems (AMS) BSIM3v3 technology and commercial IC AD844 followed by theoretical observation. Finally, experimental verification of the proposed filter is examined for the justification of our work with the help of commercially available IC AD844.